Case Report: Full recovery in severe ParvovirusB19 myocarditis with DCM phenotype: the impact of rASD and PAB - Logeswaran, T.; Akintürk, H.; Müller, M.; Rueblinger, L.; Gummel, K.; Klingel, K.; Jux, C.; Steinbrenner, B.; Schranz, D. (Frontiers in Pediatrics, 2025)
BackgroundThe incidence of parvovirus B19 (B19 V)-associated myocarditis progressing to dilated cardiomyopathy (DCM) is on the rise. We hypothesize that a comprehensive treatment regimen enables cardiac regeneration in young patients with life-threatening B19 V myocarditis.MethodsFour patients with clinical and imaging evidence of DCM were referred due to suspected myocarditis. An endomyocardial biopsy (EMB) confirmed the diagnosis. The diastolic dysfunction associated with heart failure and reduced left ventricular ejection fraction (HFrEF) was established invasively. Before surgical pulmonary artery banding (PAB), a transcatheter procedure was performed to create a restrictive atrial defect (rASD).ResultsThe drug-treated patients (ages 15–26 months) had a mean LV-EF of 22.5% (20%–25%), a left ventricular end-diastolic diameter (LVEDD) of 49 (45–51) mm (Z-score >5), and elevated LVED pressures (>18 mmHg). EMB revealed B19V-associated acute/subacute or chronic active myocarditis with characteristics of DCM. Drug therapy, including immunoglobulins and creating a rASD, resulted in clinical improvement and enhanced right ventricular function. However, LV enlargement and dysfunction persisted. Four weeks after surgical PAB, all patients showed improvement and were discharged home. The pressure gradient across the PAB ranged from 40 to 45 mmHg, and LVEDD decreased to a mean z-score of +3.5. Within three to six months, LVEDD normalized, and LV-EF increased to a mean of 63% (range: 57%–68%). Clinical and cardiac improvements were sustained over a median follow-up of 7.5 years.ConclusionA holistic treatment approach allows functional regeneration in B19 V myocarditis with obvious end-stage DCM. Restrictive ASD creation is required before surgical PAB when HFrEF is associated with a diastolic dysfunction component.